2015
DOI: 10.1162/adev_a_00047
|View full text |Cite
|
Sign up to set email alerts
|

Trilemma Challenges for the People's Republic of China

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Same findings found in Goh and McNown (2015) when reviewing the existence of Trilemma in Malaysia using Error Correction Model estimation. Kawai and Liu (2015) confirmed the same findings using monthly data for China from 1990 to 2014 when testing Trilemma challenges using generalized method of moments procedure (GMM). Majumder and Nag (2021) assessed the existence of Trilemma using quarterly data from 1991 to 2018 for India using Instrumental Variable method (IV).…”
Section: A Review On the Validity Of Trilemmasupporting
confidence: 69%
See 1 more Smart Citation
“…Same findings found in Goh and McNown (2015) when reviewing the existence of Trilemma in Malaysia using Error Correction Model estimation. Kawai and Liu (2015) confirmed the same findings using monthly data for China from 1990 to 2014 when testing Trilemma challenges using generalized method of moments procedure (GMM). Majumder and Nag (2021) assessed the existence of Trilemma using quarterly data from 1991 to 2018 for India using Instrumental Variable method (IV).…”
Section: A Review On the Validity Of Trilemmasupporting
confidence: 69%
“…Despite the multiplicity of empirical studies, both at one country level or at multi-country level, there was no consensus on the validity of Trilemma (Ihnatov and Căpraru, 2014). Some studies confirmed the validity of Trilemma such as Aizenman et al (2013); Bhatta et al (2021); Goh and McNown (2015); Hsing, 2012 a ; Kawai and Liu (2015); Majumder and Nag (2021) and You et al (2014). Others have failed to prove such Trilemma like Kim and Lee (2008) and Rey (2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, capital controls are often partially effective, and, thus, capital fl ows through non-regulated channels remain a persistent concern for the monetary authority. This is actually the case for many emerging countries and especially for China (see Baba and Kokenyne, 2011;Kawai and Liu, 2015).…”
Section: Policy Discussionmentioning
confidence: 93%
“…Evidence from emerging market economies (EMEs) also supports the impossible trilemma hypothesis. Kawai and Liu (2015) identified that China is losing its monetary policy independence due to reduced capital controls and a rigid exchange rate regime. Goh and McNown (2015) showed that the US and Malaysian interest rates cointegrated during the fixed exchange rate regime period of 2001-2005 but not during the managed float regime period of 1991-1998, providing strong evidence in favor of the impossible trinity hypothesis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The trilemma condition is further discussed in Section 3 of this study. Kim and Lee (2008); Paul (2012); You et al (2014); Kawai and Liu (2015); Goh and McNown (2015); Chakraborty (2016); Lim andGoh (2016) andDe Waal, Gupta, andJooste (2018) studied the effect of the foreign interest rate, either the London interbank offered rate (LIBOR) or the central bank policy rate, on the domestic interest rate. Most of these studies assume a reciprocal relationship between the home and foreign interest rates.…”
Section: Introductionmentioning
confidence: 99%